Clinical Awareness and Acceptance of Sonographically Diagnosed Epiploic Appendagitis (EA): A Retrospective Analysis of EA in a Single Tertiary Academic Referral Center - Safai Zadeh, Ehsan; Kindermann, Julia; Dietrich, Christoph F.; Görg, Christian; Bleyl, Tobias; Alhyari, Amjad; Trenker, Corinna (Ultrasound International Open, 2020)
Purpose To describe the clinical awareness and acceptance of ultrasound-diagnosed acute epiploic appendagitis (EA) and their importance to avoid unnecessary therapeutic and imaging measures.Patients and Methods The data were obtained of n=54 patients with acute, localized, peritonitic pain and EA diagnosed by B-mode ultrasound and contrast-enhanced ultrasound examination from November 2003 to September 2020. All examinations were performed by a German Society for Ultrasound in Medicine (DEGUM) Level III qualified examiner. Based on documentation by the treating physicians, the clinical awareness and acceptance of EA diagnosis was determined in all patients and compared between subgroups diagnosed before 2013 and from 2013 onwards. In 2013, a local educational training program regarding the diagnosis of and therapy for EA was initiated for physicians.Results In all patients, EA was sonographically diagnosed by a DEGUM level III qualified examiner. At enrollment, EA was mentioned as a suspected clinical diagnosis in n=1/54 (1.9%) patient. Furthermore, in n=39/54 (72.2%) cases, the EA was documented and accepted by the treating physicians at the time of patient discharge as the final clinical diagnosis. The clinical acceptance was significantly higher from 2013 onwards compared with before 2013 (p<0.05). Moreover, in n=26/54 (48.1%) patients, unnecessary therapeutic measures were initiated, with no significant difference between pre-2013 and post-2013 numbers (p>0.05).Conclusion In our retrospective study, we showed that awareness and acceptance of the disease EA are low. Low diagnostic acceptance of EA by the clinician leads to unnecessary therapeutic and imaging measures and is a general problem related to rare diseases in the healthcare system.
Keywords: epiploic appendagitis; abdominal ultrasonography; CEUS; clinical awareness; clinical acceptance